1993
DOI: 10.2172/10188085
|View full text |Cite
|
Sign up to set email alerts
|

Organic chemical aging mechanisms: An annotated bibliography. Waste Tank Safety Program

Abstract: An annotated bibliography has been compiled of the potential chemical and radiological aging mechanisms of the organic constituents (non-ferrocyanide) that would likely be found in the UST at Hanford. The majority of the work that has been conducted on the aging of organic chemicals used for extraction and processing of nuclear materials has been in conjunction with the acid or PUREX type processes. At Hanford the waste being stored in the UST has been stabilized with caustic. The aging factors that were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Prompted by specific questions concerning aging pathways and products, the chemical literature was searched for relevant prior work that might address the questions directly or provide insight to possible answers. Thls section summarizes these literature reviews which were performed this year on topics not covered in the annotated bibliography prepared in the previous year (Sarnuels et al 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prompted by specific questions concerning aging pathways and products, the chemical literature was searched for relevant prior work that might address the questions directly or provide insight to possible answers. Thls section summarizes these literature reviews which were performed this year on topics not covered in the annotated bibliography prepared in the previous year (Sarnuels et al 1993).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effort to understand the potential for aging or decomposition of the organic solvents in tank wastes was initiated by work at WHC (Babad et al 1993) and work at the Pacific Northwest National Laboratory (Samuels et al 1993;Camaioni et al 1994 andCamaioni et al 1996). Samuels and coworkers reviewed the literature on the base-catalyzed hydrolysis and radiation chemistry of TBP and related compounds (Samuels et al 1993). It was found that although TBP is only slightly soluble in water, it undergoes hydrolysis rather rapidly in alkaline solution to form sodium dibutylphosphate.…”
Section: -11mentioning
confidence: 99%